The G30S/PKI in modern Indonesian novels by post-reformation women authors - Efendi, Anwar; Nurgiyantoro, Burhan; Suryaman, Maman; Mashlihatin, Anis (Diksi, 2023)
Politics (facts) and literature (fiction) are two things that both exist and are needed by society. The two are also often linked together. The specific relationship between politics understood as a way of doing things and literature understood as a practical form of writing. This study uses a qualitative descriptive design to trace the re-interpretation of political facts in modern Indonesian novels written during the post-reform era. The research data sources are post-reform novels published in modern Indonesian literature that reinterpret political facts. These political facts can be found through the thematic aspects, the mindset and actions of the characters, the arrangement of the plot (conflict), and descriptions of the story setting which are integral to the whole fictional story. The determination of novels to be used as data sources is based on the following considerations: (a) novels that re-interpret political facts related to the historical events of the 30 September 1965 Movement, (b) novels published during the post-reform era (2000s and above), and (c) novels written by female authors are of a generation that did not directly experience the events of the 30 September 1965 Movement. The results of the study are as follows. First, the political facts expressed in the novel, namely (a) the kidnapping and murder of seven generals, (b) the Cakrabirawa elite troops, (c) the kidnapping and murder of people who were considered to be part of the Indonesian Communist Party, (d) detention on the island Buru, (e) granting status as a descendant of the PKI, and (f) abolishing citizenship status for students studying in certain countries deemed to be affiliated with the communist party. Second, the reinterpretation of historical facts in the novel, namely (a) related to the journey of the past, (b) part of the journey of Indonesian history, (c) understanding from the human side, and (d) choices and awareness of the journey of life in the future. It is hoped that the results of the research can be implemented in teaching literature in schools and the wider community through scientific forums in an effort to socialize the possibility of using modern literary works as a source of historical information to support efforts to understand Indonesian history. If used critically and combined with other sources, novels that actualize and reinterpret political facts can be used as a source of knowledge and understanding of the nation's history. Keywords: political facts, reinterpretation, G30S/PKI movement, modern Indonesian novels